O espaço dos mortos na cidade dos vivos: arqueologia no cemitério velho de Delmiro Gouveia, Alto Sertão de Alagoas, Brasil - Souza, Carla Janine Vieira de (2024)
Subjects related to the funerary universe are a relatively new research area in Brazil. However, over the years, there has been significant deepening of the theme of death, the dead, and dying, especially since the 2000s (IPHAN, 2024), a period when these approaches gained greater prominence and depth. Today, it is possible to access excellent quality productions in various fields of knowledge dedicated to this perspective, as well as debates involving cemetery studies (MAGALHÃES, 2018). The object of this research is the municipal cemetery, popularly known as the old cemetery, located in Delmiro Gouveia, a city in the Alto Sertão region of Alagoas, Northeast Brazil. The objective is to analyze and discuss changes and continuities concerning specific burial spaces, which we refer to as tombs. For this, bibliographical, documentary, and photographic surveys were conducted, along with a detailed analysis of the cemetery's materiality. As a result, we identified five distinct phases of the cemetery's funerary material culture: the first phase, from 1908 to the 1920s; the second phase, from the 1930s to the 1940s; the third phase, from the 1950s to the 1970s; the fourth phase, from the 1980s to the 1990s; and the fifth phase, from the 2000s to the present day. In this context, we observed transformations in the graves and the adornments that make up the funerary structure. These changes were evidenced through construction materials, adornments, iconography, and the tomb architecture itself. Despite the transformations, we found that the old and new still coexist, sharing the same space and time.